TRANSPORT COSTS AND THE LOCATION OF INDUSTRIES IN IBADAN – A STUDY IN INDUSTRIAL GEOGRAHY (1968)
The significance of transport costs in the location of industries in Ibadan is studied through the application of the comparative cost approach while spatial differential in factor costs is investigated by means of field survey and statistical methods. The theoretical schema which formalizes the comparative cost approach is substitution of production factors. This considers alternative locations in terms of substitution between transport costs and processing costs and identifies the least cost location. Industrial concentration in Ibadan is assessed through the adaptation of the multiple criteria technique. The result shows that the magnitude of manufacturing in Ibadan is 50.60% of the total for Western Nigeria. In Ibadan one universal element of production factors which varies significantly from industry to industry and which is generally subject to persistent spatial variation is transport cost. The role of transport costs in attracting industries into Ibadan is found to be very important in the Fruit Canning and Orange Squash industries but much less so with regards to Soft Drinks and Furritture. These latter have been attracted to Ibadan by the available metropolitan market advantages which form, the basis of the present unique spatial monopoly enjoyed by Ibadan in the location of Industries. Results of cost calculations and perhaps most importantly transport costs are generally compatible with similar studies emphasizing the significance of transport costs in the location of specific industries elsewhere. The location of other industries not considered here for lack of data will have to await future Investigation.